Defining Left Ventricular Hypertrophy in Children on Peritoneal Dialysis - Borzych, Dagmara (American Society of Nephrology, 2011)
SUMMARY: BACKGROUND AND OBJECTIVES: Left ventricular hypertrophy (LVH) is an important end point of dialysis-associated cardiovascular disease. The objective of this study was to evaluate the effect of different pediatric reference systems on the estimated prevalence of LVH in children on chronic peritoneal dialysis (CPD). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Echocardiographic studies in 507 pediatric CPD patients from neonatal age to 19 years were collected in 55 pediatric dialysis units around the globe. We compared the prevalence of LVH on the basis of the traditional cutoff of left ventricular mass (LVM) index (>38.5 g/m(2.7)) with three novel definitions of LVH that were recently established in healthy pediatric cohorts. RESULTS: Application of the new reference systems eliminated the apparently increased prevalence of LVH in young children obtained by the traditional fixed LVM index cutoff currently still recommended by consensus guidelines. However, substantial differences of LVM distribution between the new reference charts resulted in a marked discrepancy in estimated LVH prevalence ranging between 27.4% and 51.7%. CONCLUSIONS: Although our understanding of the anthropometric determinants of heart size during childhood is improving, more consistent normative echocardiographic data from large populations of healthy children are required for cardiovascular diagnostics and research.